CircRNA_0048211 protects postmenopausal osteoporosis through targeting miRNA-93-5p to regulate BMP2 - Qiao, L; Li, C-G; Liu, D (European review for medical and pharmacological sciences, 2020)
The purpose of this study was to elucidate the potential influence of circular RNA (circRNA)_0048211/miRNA-93-5p/BMP2 regulatory loop in the progression of postmenopausal osteoporosis (PMOP). Bone marrow samples were collected from PMOP patients (n=30) and healthy subjects (n=30) for isolating hBMSCs. Relative levels of circRNA_0048211, miRNA-93-5p, and BMP2 in hBMSCs isolated from PMOP patients and healthy controls were detected. In addition, their dynamic expressions in hBMSCs isolated from PMOP patients undergoing osteogenesis for 0, 7, 14, and 21 days were examined. Then, the interaction in the circRNA_0048211/miRNA-93-5p/BMP2 regulatory loop was verified by Dual-Luciferase reporter gene assay. Next, the potential influences of circRNA_0048211/miRNA-93-5p/BMP2 regulatory loop on osteogenesis-associated gene expressions, ALP activity, and mineralization ability were assessed. CircRNA_0048211 and BMP2 were downregulated, while miRNA-93-5p was upregulated in hBMSCs isolated from PMOP patients. In hBMSCs undergoing osteogenesis, circRNA_0048211, miRNA-93-5p and BMP2 were time-dependently changed. Overexpression of circRNA_0048211 upregulated RUNX2, OPN, and OCN, which also stimulated ALP activity and mineralization ability. CircRNA_0048211 could bind to miRNA-93-5p, and BMP2 was a direct target of miRNA-93-5p. In the meantime, circRNA_0048211 was negatively correlated with miRNA-93-5p, and positively correlated with BMP2. Besides, CircRNA_0048211/miRNA-93-5p/BMP2 regulatory loop was responsible for regulating osteogenesis-associated gene expressions, ALP activity, and mineralization ability in hBMSCs. CircRNA_0048211 negatively targets miRNA-93-5p to upregulate BMP2, thus alleviating the progression of PMOP.